Signless Laplacian Spectral Conditions for Hamiltonicity of Graphs. (30th June 2014) - Yu, Guidong; Ye, Miaolin; Cai, Gaixiang; Cao, Jinde
Abstract : We establish some signless Laplacian spectral radius conditions for a graph to be Hamiltonian or traceable or Hamilton-connected.